An Analysis Of The Creative Process In Creating Recycled Artwork Among Fourth-Grade Elementary School Students - Indriyani Indriyani; Arna Juwairiyah; Sri Marliah Puteri (CV. Gerasi Insan Nusantara, 2025)
This study aims to describe the creative process of fourth-grade students in producing recycled artworks from used materials based on Wallas’s stages of creativity and to identify the factors influencing this process. The study employed a qualitative approach with a descriptive research design. The participants consisted of a fourth-grade teacher and 12 fourth-grade students who were purposively selected because they were directly involved in recycled art learning activities. Data were collected through observation, semi-structured interviews, and documentation and were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing and verification. Data credibility was established through source triangulation, technique triangulation, and member checking. The findings indicate that students’ creative processes developed through four stages: preparation, incubation, illumination, and verification. During the preparation stage, students understood the task and explored the characteristics and potential uses of used materials. The incubation stage was characterized by the development and refinement of ideas through reflection and discussion. During the illumination stage, students transformed their ideas into creative and varied artworks, while the verification stage was demonstrated through the evaluation and refinement of the artworks based on self-reflection and teacher feedback. The creative process was influenced by internal factors, including motivation, interest, self-confidence, and perseverance, as well as external factors, including the teacher’s role, peer interaction, and the use of used materials as learning media. The findings demonstrate that recycled art learning not only develops students’ creativity but also strengthens critical thinking, collaboration, communication, and environmental awareness. This study provides an empirical contribution to the development of art learning oriented toward the creative process and the strengthening of 21st-century competencies in elementary education.